Pseudoepitheliomatous hyperplasia causing a painful plaque in a HIV-infected female. (June 2017) - Parsons, Bianca F; Ryder, N
Dermatological conditions are more common and can present atypically, in human immunodeficiency virus-infected individuals. This case report describes a 22-year-old human immunodeficiency virus-positive Caucasian female who presented with a vulval lesion eight weeks after starting antiretroviral treatment. Clinical examination revealed a 2 cm well-demarcated plaque on the outer aspect of the left labium minus. The lesion was tender, no contact bleeding or ulceration present. She was presumptively treated for chancroid and herpes simplex with 500 mg ceftriaxone IM stat, 1 g azithromycin PO stat, and valacyclovir 500 mg BD for five days. The lesion persisted despite treatment, and during follow-up, a punch biopsy was carried out. She was diagnosed with pseudoepitheliomatous hyperplasia of the epidermis. In addition to highlighting this condition that has been previously reported in human immunodeficiency virus/herpes simplex virus co-infection, this case demonstrates that unusual skin presentations must be considered in human immunodeficiency virus-infected individuals and illustrates the importance of biopsy for any non-healing lesions.